Register to reply

Forming a formula from a-b=c-d

by khazaymeh
Tags: abcd, forming, formula
Share this thread:
khazaymeh
#1
Mar26-14, 10:10 AM
P: 2
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
Phys.Org News Partner Mathematics news on Phys.org
Researcher figures out how sharks manage to act like math geniuses
Math journal puts Rauzy fractcal image on the cover
Heat distributions help researchers to understand curved space
phinds
#2
Mar26-14, 10:19 AM
PF Gold
phinds's Avatar
P: 6,509
Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
c=a-b+d follows directly from the stated relationship. Where did you get c=a/b*d ???
Mark44
#3
Mar26-14, 10:24 AM
Mentor
P: 21,407
Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
What you got above is correct. To solve for c, add d to both sides of the equation.

I don't know how you got the equation below, but it's incorrect.
Quote Quote by khazaymeh View Post
and c=a/b*d

can I use any other formulas?!!
The equation you started with is very simple, so the only possible differences are how the three terms on the other side are arranged, with a total of six ways.

c = a - b + d
c = a + d - b
c = d + a - b
c = d - b + a
c = -b + a + d
c = -b + d + a

craigi
#4
Mar26-14, 10:24 AM
P: 428
Forming a formula from a-b=c-d

Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
c=a-b+d follows from a-b=c-d

c=a/b*d follows from a/b=c/d

Did you write it down in a way that your -'s look like /'s ?


Register to reply

Related Discussions
Formula forming for Motion in Space General Math 0
Forming a series Calculus & Beyond Homework 1
Forming ln(y)= into y= Calculus & Beyond Homework 1
Forming differential equations..from words to formula Calculus & Beyond Homework 7
Forming DE Differential Equations 4